2016
DOI: 10.1371/journal.pone.0146171
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Incidence of Acute Infectious Intestinal Disease in the Community in the UK: A Retrospective Telephone Survey

Abstract: ObjectivesTo estimate the burden of intestinal infectious disease (IID) in the UK and determine whether disease burden estimations using a retrospective study design differ from those using a prospective study design.Design/SettingA retrospective telephone survey undertaken in each of the four countries comprising the United Kingdom. Participants were randomly asked about illness either in the past 7 or 28 days.Participants14,813 individuals for all of whom we had a legible recording of their agreement to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
3
11
2
Order By: Relevance
“…As reported in previous studies [12,14], the GII incidence in the present study was affected by recall time. This may be linked to a recall bias commonly known as telescoping, where participants remember disease episodes as occurring more recently than they actually were.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As reported in previous studies [12,14], the GII incidence in the present study was affected by recall time. This may be linked to a recall bias commonly known as telescoping, where participants remember disease episodes as occurring more recently than they actually were.…”
Section: Discussionsupporting
confidence: 79%
“…European studies have reported incidence ranging from 0.27 to 1.4 AGI episodes per person-year [10][11][12][13][14][15][16][17][18]. Most of the previous estimates are for the total population, including children, thus partly explaining the low AGI reported in our study.…”
Section: Discussioncontrasting
confidence: 41%
“…Retrospective studies in the UK (IID2) gave higher estimates of disease burden than prospective studies [ 19 ]. However, retrospective studies with longer recall periods gave lower estimated rates than studies with shorter recall periods [ 44 ]. Extrapolation from a reported seven-day prevalence was almost twice the rate of illness estimated when extrapolating from the month recall period [ 6 , 35 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, loss to follow up is a further disadvantage of prospective studies, which may occur already at 1 month of follow up [9]. Recently, Viviani et al [10] compared the incidence estimates of AGI in their retrospective telephone survey with another study with prospective data collection during the same time period [11], and found higher incidence estimates in the retrospective data collection for the general population. But publications explicitly comparing prospective and retrospective data collection for AGI in the households with children attending day care are scarce.…”
Section: Introductionmentioning
confidence: 99%